Parasite control and assessment of trypanotolerance - D'Ieteren, G.D.M.; Wissocq, N.M.; Trail, J.C.M.; Nantulya, V.M.; Masake, R. (OAU/STRC, 1999)
The exploitation of resistance traits very much relies on the understanding of the mechanisms underlying trypanotolerance, their characterisation in the field, the identification of practical measures of trypanotolerance characteristics, the evaluation of their linkage with final livestock outputs and finally the genetic component underlying them. Genetic progress through selection for trypanotolerance relies on criteria that can be considered as indicative of trypanotolerance. Experimental and field studies indicated that trypanotolerance is associated with the capacity to control the intensity, prevalence and duration of parasitaemia; to resist the Development of severe anaemia as measured by PCV and that, although these criteria influence each other, they are likely to operate independently. The success of any such criteria for identification of trypanotolerant breeds of cattle and/or of superior animals within these breeds depends on their practical measurement, the strength of their linkage with the economically important production traits including viability, reproductive performance and growth and of the associated genetic parameters. Quantification of the relative importance of the phenotypic and genetic components of each measure in a range of trypanosome infection situation and for different age groups is a pre-requisite to their practical and sustainable application. The objectives of our field-based research represent a series of logical steps in the process of developing support systems for on-farm selection decisions. This paper is more specifically focusing on the identification and use of aspects of trypanosome Development control capability in N'Dama cattle as criteria for assessment of trypanotolerance levels in individual animals.